PENGAWASAN PELAKSANAAN FUNGSI RUANG TERBUKA HIJAU - Febri Yuliani, Dina Anggraini, Zaili Rusli, (Jurnal Ilmu Administrasi Negara, 2019)
Supervision of the Implementation of Green Open Space Functions. This studyaims to determine the supervision of the implementation of the green open space function of thePekanbaru City government. This study uses a descriptive qualitative approach with primary dataobtained from interviews with informants. The research informants were the head of the greenopen space, employees of the field of work, community and street vendors. The results of thisstudy indicate that the supervision of the implementation of the green open space function of thedaughter of Pekanbaru by the government of Pekanbaru City has not achieved the expected results.Where in the implementation there are factors that can influence the supervision. These factors arecommunication, human resources, and community participation itself which has not beenmaximally carried out so that the supervision is also not optimal.